2017
DOI: 10.1017/s0007485317000530
|View full text |Cite
|
Sign up to set email alerts
|

Coffee berry borer in conilon coffee in the Brazilian Cerrado: an ancient pest in a new environment

Abstract: The aim of this study was to verify the occurrence of the coffee berry borer, Hypothenemus hampei (Ferrari), and to evaluate the population fluctuation of the pest in the Brazilian Cerrado (Federal District). The study was conducted, between November 2014 and October 2015, at Embrapa Cerrados (Planaltina/DF, Brazil) in an irrigated conilon coffee production area. In November 2014, 120 samples (ten berries/sample) were collected from berries that had fallen on the ground from the previous harvest. Between Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Surveys carried out in Hawaii showed that the peaks of infestations of flying adults occurred close to the harvest time and coincided with the high infestations of berries; however, a large variation in trapping was found within the same property and among properties, with an increase in infestation level in the second and third generation of CBB (Aristizábal et al, 2017a, b). Similarly, the population of CBB in Brazil is negatively correlated with the intensity of rainfall, and the highest adult populations occur in the dry season (May -August) with population peaks at the end of the harvest season (July -August) (Ferreira et al, 2000;Oliveira et al, 2018;Souza;Reis, 1997). The first spraying of insecticides was carried out within the CBB transit season, ~ 90 days after the main flowering that occurred from October 7 to November 11, 2018 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys carried out in Hawaii showed that the peaks of infestations of flying adults occurred close to the harvest time and coincided with the high infestations of berries; however, a large variation in trapping was found within the same property and among properties, with an increase in infestation level in the second and third generation of CBB (Aristizábal et al, 2017a, b). Similarly, the population of CBB in Brazil is negatively correlated with the intensity of rainfall, and the highest adult populations occur in the dry season (May -August) with population peaks at the end of the harvest season (July -August) (Ferreira et al, 2000;Oliveira et al, 2018;Souza;Reis, 1997). The first spraying of insecticides was carried out within the CBB transit season, ~ 90 days after the main flowering that occurred from October 7 to November 11, 2018 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Published recommendations for an IPM program designed for the CBB in Hawaii include field monitoring, use of B. bassiana and other insecticides, field sanitation, and post-harvest control (Kawabata et al, 2017;Aristizábal, 2018b). Various IPM strategies for the CBB have been recommended in other regions of the world, including Colombia (Bustillo et al, 1998;Benavides et al, 2002;Aristizábal et al, 2012), Mexico (Barrera et al, 1990), Brazil (Pereira et al, 2012;Olivera et al, 2018), and Africa (Kucel et al, 2009). While an IPM approach is needed, the relatively high cost of field labor in Hawaii remains a limitation for cultural pest control.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on the use of these traps for CBB monitoring, consensus remains elusive regarding trap spacing and catch data interpretation, limiting the precision of IPM strategies (Mathieu et al, 1997b;Mathieu et al, 1999;Fernandes et al, 2011;Messing, 2012;Pereira et al, 2012;Aristizábal et al, 2017;Johnson et al, 2018;Oliveira et al, 2018;Souza et al, 2020;Manoukis, 2020, 2021;Ruiz-Diaz and Rodrigues, 2021).…”
Section: Introductionmentioning
confidence: 99%